La recepción de los estereotipos y tópicos amatorios clásicos en "Os poemas possíveis" de José Saramago - Rodríguez Herrera, Gregorio (Ágora: estudos clássicos em debate, 2020)
The analysis of the poems grouped under the title ʺNesta esquina do tempoʺ shows that stereotypes and topics used in Latin love poetry are subverted and rewritten by José Saramago in order to render his poetic intention. Besides, it is argued that these stereotypes and topics must be considered another element of the inherited literary tradition present in his poetry.